Vertebrates of the Last Interglaciation in Canada: A Review, with New Data - Harington, C. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1990)
ABSTRACTVertebrate fossils and faunas that are reasonably inferred to be of last (Sangamonian) interglacial age are considered in geographic order from east to west to north in Canada. Data on localities, vertebrate taxa, stratigraphy, geochronology, paleoenvironment and paleoclimate are considered. Information on key faunas from Toronto, Fort Qu'Appelle, Saskatoon. Medicine Hat and Old Crow River is supplemented by data on smaller faunas and, in some cases, individual specimens. New data are included for several localities. Fishes, such as whitefish (Coregonus sp.) and pike (Esox sp.). had broad distributions from eastern to northwestern Canada. Except for a turtle (Emydoidea blandingi) from lnnerkip, Ontario, amphibians and reptiles have not yet been reported from Canada during the Sangamon Interglaciation. Several species of grouse-like birds (Tetraonidae) are known from western Canada. Among the mammals. American mastodons (Mammut americanum), mammoths (Mammuthus sp.), beavers (Castor canadensis), giant beavers (Castoroides ohioensis), muskrats (Ondatra zibethicus), voles (Microtus sp.). white-tailed deer (Odocoileus virginianus), stag moose (Cervalces sp.), bison [perhaps mainly giant bison (Bison latifrons)\ and muskoxen (Ovibovini) were evidently most widespread during the last interglacial interval. The western plains had a characteristic large mammal fauna that included Columbian mammoths (Mammuthus columbi), Scott's horses (Equus scotti), small horses (Equus conversidens), western camels (Camelops hesternus). pronghorns (Antilocapridae), giant bison (Bison latifrons) and helmeted muskoxen (Sy m bos cavifrons).